2021
DOI: 10.1016/j.chaos.2021.110788
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical analysis of a stochastic model for spread of Coronavirus

Abstract: This paper is associated to investigate a stochastic SEIAQHR model for transmission of Coronavirus disease 2019 that is a recent great crisis in numerous societies. This stochastic pandemic model is established due to several safety protocols, for instance social-distancing, mask use and quarantine. Three white noises are added to three of the main parameters of the system to represent the impact of randomness in the environment on the considered model. Also, the unique solvability of the presented stochastic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 24 publications
0
18
0
1
Order By: Relevance
“… [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] .…”
Section: Uncited Referencesunclassified
“… [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] .…”
Section: Uncited Referencesunclassified
“…In general, different stochastic computations [7,8] and numerical methods [9][10][11][12][13][14] are exploited to assess the various aspects of the COVID-19 outbreak. In this sense, Katoch et al used the autoregressive integrated moving average (ARIMA) model to forecast the COVID-19 dynamics in India [15].…”
Section: Sars-cov-2 (Covid-19mentioning
confidence: 99%
“…However, while checking with great care predictions done while using this analysis, one will easily see that this analysis cannot help humans predict waves in spread. For example, several mathematical models have been suggested to predict the spread of Covid-19, unwillingly no analysis help to predict the numbers of waves that humans will faced by Covid-19 spread [5][6][7][8][9][10][11][12]. In fact, some researchers showed that, the reproductive number was not su¢ cient to provide a clear behavior of the spread, although no attention was paid to such analysis, one will agree that suggested mathematical models and analysis done in the last decades have not really help to predict waves.…”
Section: Introductionmentioning
confidence: 99%